Analisis Pengaruh Tingkat Pendidikan, Angkatan Kerja dan Pengeluaran Pemerintah Terhadap PDRB di Provinsi Sumatera Selatan - Riza Fahlewi; Riki Chairul Amri; Adesy Mayang Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Economic growth measures the performance of an economy's development from one period to the next. The research objective was to analyze the effect of education level, labor force and government expenditures on GRDP in South Sumatera Province. The data used was secondary data from Revenue Office of Financial Management and Regional Assets and Central Bureau of Statistics (BPS) South Sumatera Province for 6 years (2013-2018). It was concluded that the variables of education has not significant effect on GRDP, while labor force, government expenditureshas significant effect on GRDP. The quantity of labor force contributes to economic growth and increased government expenditures should be balanced with the success of development in various sectors and fields. Keywords: GRDP, Education, Labor Force, Government Expenditures